Uma metodologia para implementação de tecnologia CNC em máquinas seccionadoras - Santos, Jeferson Rafael Rodrigues dos (2012)
This work consists in proposing a methodology for the conversion of conventional sectioning machines in CNC equipments. The study is directed to the furniture industry and considers the possibility to outfit this kind of equipment with two programmable motion axes, through the utilization of devices as linear guides activated by engines with positioning accuracy. The system specifies one of the axes for motion and positioning of the plate to be counted, according to the dimensions of the project and other axis for the displacement of the limit sensor of the cutting tool. The technique consists in generating automatically the CNC programs for the adapted machine with data coming from systems of cutting plans generation. This work shows how to implement this technique through CAD application and considers two possibilities of obtaining the Cutting Plan data. On the first case, the sequence of cutting, defined with specialized computer programs, is converted in a drawing on CAD, that after is processed for the generation of the CNC program to the machine. The other alternative is to consider the possibility to implement techniques dedicated to the definition of the cutting arrangement, through CAD routines. In this case, a manual method was purposed with the goal to demonstrate the technique that assumes that the furniture project is virtually defined on CAD through 3D drawing resources. To demonstrate the validity of the methodology were elaborated two virtual projects a kitchen and a bedroom for which were generating the cutting plans with different techniques and their CNC programs. This study shows that the number of patterns produced for cutting planes through the proposed empirical method for a software used is the same. However, note that there is a difference in the occupied area, comparing the use of sheet parts in the software and the empirical method, it would not be feasible due to the sum of surpluses generated a longer period of production.